Implementation of Civic Education in Building the Nation's Character (Wiyatamandala, 2025)
Pancasila education is one of the most important factors and needed in building the nation's character based on Pancasila values, which are the basis of the ideology of the Indonesian state. This journal aims to investigate how PKn is implemented in schools in Indonesia and how it impacts the formation of students' character. In this qualitative research, data was collected through observation, comprehensive interviews, and documentation investigations from various sources. This study shows that the effective use of PKn increases national and state awareness and instills national values such as tolerance, justice, and solidarity. The study also found problems in implementing PKn, such as a lack of teacher training and limited resources. Based on these findings, this journal provides recommendations to improve the PKn curriculum to make it more relevant and relevant. The journal also emphasizes how important it is for schools, parents, and communities to work together. in implementing PKn, such as limited resources and lack of teacher instruction. Based on these findings, the journal provides recommendations to make the PKn curriculum more relevant and relevant, as well as on the importance that schools, parents, and communities work together to support character education. Therefore, it is hoped that PKn can contribute significantly to the formation of a young generation that is not only academically good but also physically strong and responsible as citizens.